2006
DOI: 10.5458/jag.53.27
|View full text |Cite
|
Sign up to set email alerts
|

Process for Producing Brown Rice with Increased Accumulation of GABA Using High-pressure Treatment and Properties of GABA-increased Brown Rice

Abstract: Brown rice is commonly considered to have an effect on various diseases including life-style related diseases. Pre-germinated brown rice is characterized by its easier cooking properties and better taste after cooking when compared with normal brown rice. Because of the rich content of gamma-aminobutyric acid (GABA) in brown rice, which can prevent the increase of blood pressure, the market for brown rice is now growing. However, the taste of the cooked pre-germinated brown rice is still unsatisfactory because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…For example, the GABA levels of GABA-rich tomatoes and pumpkins have been reported to be approximately 1000 mg/100 g and 500 mg/100 g, respectively (Watanabe et al, 2013;Akihiro et al, 2008). On the other hand, the levels in GABA-rich rice have been reported to be 20 _ 40 mg/100 g (Sasagawa et al, 2006;Lu et al, 2010). The GABA content in our prepared sesame seeds was calculated to be 43.3 mg/100 g. This content is almost the same as that of GABArich rice.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the GABA levels of GABA-rich tomatoes and pumpkins have been reported to be approximately 1000 mg/100 g and 500 mg/100 g, respectively (Watanabe et al, 2013;Akihiro et al, 2008). On the other hand, the levels in GABA-rich rice have been reported to be 20 _ 40 mg/100 g (Sasagawa et al, 2006;Lu et al, 2010). The GABA content in our prepared sesame seeds was calculated to be 43.3 mg/100 g. This content is almost the same as that of GABArich rice.…”
Section: Figmentioning
confidence: 99%
“…The GABA-accumulation phenomenon has been utilized to enrich GABA content of fruits, vegetables and other plant materials. The process includes anaerobic CO 2 , highpressure and immersion treatments (Saikusa et al, 1994;Sasagawa et al, 2006;Wang et al, 2006;Komatsuzaki et al, 2007;Akihiro et al, 2008;Watanabe et al, 2013).…”
mentioning
confidence: 99%
“…Sasagawa et al reported that the concentration of gamma-amimobutyric acid in pressure treated brown rice increased during preservation at moderate temperature. 8) This finding could be well explained by the alternation of foodstuffs induced by HPP described above. In the view of noble use of HPP enabling addition of values on foodstuffs, it is important to analyze biochemical changes of foodstuffs during storage after HPP.…”
mentioning
confidence: 75%
“…In addition, its mouthfeel, digestion, and absorption in the intestine are improved by free sugars, such as glucose or oligosaccharides, generated from starch hydrolysis during germination. Thus, GBR is improved, not only in functionality, but also in palatability and convenience, compared to BR (Kim et al ., 2006; Sasagawa et al ., 2006). In addition, it is known that most grains have an antinutrient factor, such as phytate.…”
Section: Introductionmentioning
confidence: 99%